Expedient synthesis of 1,2,3-triazole-fused tetracyclic compounds by intramolecular Huisgen ('click') reactions on carbohydrate-derived azido-alkynes - Hotha, Srinivas; Anegundi, Ramakrishna I.; Natu, A. A. (Tetrahedron Letters, 2005)
An efficient, practical and convenient synthesis of 1,2,3-triazole-fused tetracyclic compounds was achieved by intramolecular 1,3-dipolar cycloaddition of carbohydrate-derived azido-alkynes. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: carbohydrates; Click chemistry; Cycloaddition; diversity oriented synthesis; Huisgen reaction

Efficient synthesis of azetidine-2,3-diones from L-(+)-diethyl tartrate - Chincholkar, Pinak M.; Puranik, Vedavati G.; Deshmukh, Abdul Rakeeb A. S. (Synlett, 2007)
A convenient route to enantiopure azetidine-2,3-diones is described. The chiral ketene generated from commercially available L-(+)-diethyl tartrate on Staudinger cycloaddition with different imines gave spiro-beta-lactams in good yields. These spiro-beta-lactams were transformed into azetidine-2,3-diones in excellent yields in a two-step process.
Keywords: Cycloaddition; imines; lactams; spiro compounds; stereoselective synthesis

MoO3/SiO2: an efficient and selective catalyst for the synthesis 1,3-dioxolane and 1,3-dioxane - Amrute, Amol P.; Sahoo, Suman; Bordoloi, Ankur; Hwang, Young Kyu; Hwang, Jin-Soo; Halligudi, Shiva B. (Catalysis Communications, 2009)
A series of MoO3/SiO2 catalysts with varying amounts of MoO3 has been synthesized and the catalytic activities of these were compared with the known solid acid catalysts in the synthesis of 1,3-dioxolane. MoO3/SiO2 catalyst showed a better activity and selectivity in 1,3-dioxolane synthesis compared to the other catalysts. MoO3/SiO2 catalyst system was further successfully applied for the synthesis of 1,3-dioxanes in the Prins cyclization of olefins and formaldehyde. The proposed catalyst was thermally stable and could be recovered and reused at least in four consecutive cycles with no significant loss in the substrates conversions and products selectivities. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: 1; 3-Dioxolanes; Cycloaddition; MoO3/SiO2; Prins cyclization; Sol-gel method; solid acid catalysts

Click chemistry: 1,2,3-triazoles as pharmacophores - Agalave, Sandip G.; Maujan, Suleman R.; Pore, Vandana S. (Chemistry-an Asian Journal, 2011)
The copper(I)-catalyzed 1,2,3-triazole-forming reaction between azides and terminal alkynes has become the gold standard of `click chemistry' due to its reliability, specificity, and biocompatibility. Applications of click chemistry are increasingly found in all aspects of drug discovery; they range from lead finding through combinatorial chemistry and target-templated in vitro chemistry, to proteomics and DNA research by using bioconjugation reactions. The triazole products are more than just passive linkers; they readily associate with biological targets, through hydrogen-bonding and dipole interactions. The present review will focus mainly on the recent literature for applications of this reaction in the field of medicinal chemistry, in particular on use of the 1,2,3-triazole moiety as pharmacophore.
Keywords: Click chemistry; Copper; Cycloaddition; pharmacophores; triazoles

Construction of the 5,10b-phenanthridine skeleton using [3+2]-cycloaddition of a non-stabilized azomethine ylide: total synthesis of (+/-)-maritidine and (+/-)-crinine alkaloids - Pandey, Ganesh; Gupta, Nishant R.; Gadre, Smita R. (European Journal of Organic Chemistry, 2011)
Vicinal quaternary and tertiary stereocenters of the 5,10b-phenanthridine skeleton 1 are constructed simultaneously in one step by the [3+2]-cycloaddition of non-stabilized azomethine ylide 9, generated by sequential double desilylation of 10 utilizing silver(I) fluoride as a one-electron oxidant. The regioas well as stereochemical origin of this cycloaddition reaction is explained through a favorable transition state 9''. The strategy is successfully applied for the total synthesis of the biologically active alkaloids (+/-)-maritidine (1a), (+/-)-crinine (1b), and their analogues (1d, 1e, and 1f).
Keywords: alkaloids; Azomethine ylides; Cycloaddition; Natural products; Ylides

Eutectic mixture-directed kinetics of Diels-Alder reaction - Nagare, Amit S.; Kumar, Anil (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2011)
In the search for environmentally benign solvent media, a new class of solvents composed of mixtures of carbohydrates with urea or methylated urea has been noted to be effective in enhancing the reaction rates of a bimolecular organic reaction like the Diels-Alder reaction of cyclopentadiene with methyl acrylate. The viscosity of these media appears to be an important parameter in controlling the second order kinetics.
Keywords: carbohydrates; Cycloaddition; Diels-Alder reaction; Dimethylurea; kinetics; Reaction rates; solvent effects; Urea; viscosity

One-step stereospecific strategy for the construction of the core structure of the 5,11-methanomorphanthridine alkaloids in racemic as well as in optically pure form: synthesis of (+/-)-pancracine and (+/-)-brunsvigine - Pandey, Ganesh; Kumar, Ravindra; Banerjee, Prabal; Puranik, Vedavati G. (European Journal of Organic Chemistry, 2011)
The unique core structure of the complex pentacyclic 5,11-methanomorphanthridine has been constructed stereospecifically in one step by an intramolecular [3+2] cycloaddition of a non-stabilized azomethine ylide (AMY), generated by the sequential double desilylation of 14 using (AgF)-F-I as a one-electron oxidant. The formation of the single diastereomer in the key step is explained by the preferred transition state produced by endo attack of the AMY on the ``Re'' face of the dipolarophile. An asymmetric version of the cycloaddition using a chiral dipolarophile was applied to construct the core structure 68 with 63 % ee. This strategy was successfully applied to the formal synthesis of (+/-)-pancracine and the total synthesis of (+/-)-brunsvigine. An unprecedented and interesting skeletal rearrangement product 49 was observed during the attempted assembly of the E ring from 46 through Horner-Wadsworth-Emmons reactions. Mechanisms involving azetidinium salt formation or the Grob-type fragmentation are advanced to explain the observed rearrangement.
Keywords: alkaloids; Azomethine ylides; Cycloaddition; Ring-closing metathesis; synthesis design

Alumina-supported copper iodide: an efficient and recyclable catalyst for microwave-assisted synthesis of 1,4-disubstituted 1,2,3-triazoles via three-component reaction in water - Agalave, Sandip G.; Pharande, Shrikant G.; Gade, Swapna M.; Pore, Vandana S. (Asian Journal of Organic Chemistry, 2015)
A one-pot procedure for the synthesis of 1,4-disubstituted 1,2,3-triazoles by a three-component reaction of allyl or benzyl halides, sodium azide, and terminal alkynes over a neutral alumina-supported copper iodide catalyst has been developed. The products were isolated by simple filtration followed by washing of the catalyst with acetone. The products were obtained in almost pure form in up to 98% yield (TON 495). The catalyst can be recycled for more than eight subsequent reactions. The halides are directly converted into triazoles via in situ formation of azides and thus handling of hazardous azides can be avoided. The broad scope of this protocol is shown by the synthesis of a variety of diversely substituted 1,2,3-triazoles and also two-component azide-alkyne click reaction. The key features of this procedure are the use of water as a solvent, recyclability of the catalyst up to eight runs without appreciable loss of activity, and high yields of products. The catalyst has been fully characterized by FTIR, solid-state NMR and EDX spectroscopy, ESEM, TGA, and XRD.
Keywords: 1; 2; 3-triazoles; 4; copper(I) iodide; Cycloaddition; disubstituted 1; Microwave chemistry; supported catalysts

Design and synthesis of 11 alpha-substituted bile acid derivatives as potential anti-tuberculosis agents - Pore, Vandana S.; Divse, Jaisingh M.; Charolkar, Chaitanya R.; Nawale, Laxman U.; Khedkar, Vijay M.; Sarkar, Dhiman (Bioorganic & Medicinal Chemistry Letters, 2015)
We have synthesized a series of novel 11 alpha-triazoyl bile acid derivatives. In addition, we also have synthesized N-alkyl and N-acyl derivatives of C-11 amino bile acid esters. All the compounds were evaluated for the inhibitory activity against Mycobacterium tuberculosis H37Ra (MTB) at 30 mu g/mL level. Four lead compounds (2b, 3, 7 and 8) were further confirmed from their dose dependent effect against MTB. These compounds were found to be active against Dormant and active stage MTB under both in vitro as well as within THP1 host macrophages. The most promising compound 2b showed strong antitubercular activities against MTB under in vitro and ex vivo (IC90 value of similar to 3 mu g/mL) conditions and almost insignificant cytotoxicity up to 100 mu g/mL against THP-1, A549 and PANC-1 human cancer cell lines. Inactivity of all these compounds against Gram positive and Gram negative bacteria indicates their specificity. Molecular docking studies of these compounds into the active site of DprE1 enzyme revealed a similar binding mode to native ligands in the crystal structure thereby helping to establish a structural basis of inhibition of MTB. The synthesized compounds were analyzed for ADME properties and showed potential to develop good oral drug candidates. Our results clearly indicate the identification of some novel, selective and specific inhibitors against MTB that can be explored further for potential antitubercular drug. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Antituberculosis; Bile acids; Cycloaddition; Docking study; In silico ADME

Synthesis and characterization of D-2PA-Pd(II)@SBA-15 catalyst via ``click chemistry'': highly active catalyst for Suzuki coupling reactions - Pathak, Aruna; Singh, A. P. (Journal of Porous Materials, 2017)
Copper catalysed cycloaddition reaction between azide and terminal alkyne, called as ``click reaction'', was found to be modular approach for the synthesis of facile, highly efficient and recoverable D-2PA-Pd(II)@SBA-15 catalyst. In efforts to synthesize the catalyst, the cycloaddition reaction between azido-functionalized mesoporous SBA-15 and N,N-dimethyl-2-propynylamine (D-2PA) has been carried out, followed by the complexation with PdCl2. To analyze physiochemical properties of synthesized materials, various characterization techniques such as CHN elemental analysis, X-ray diffraction, solid state C-13 and Si-29 NMR spectra, FT-IR, XPS, SEM, TEM and N-2 sorption analysis, TGA and DTA, UV-Vis spectroscopy have been carried out. The synthesized catalyst, D-2PA-Pd(II)@SBA-15, exhibited excellent catalytic activities with good product yield and high TON towards Suzuki coupling reaction of various aryl halides with phenylboronic acid. The effect of solvent, base and temperature on coupling reactions has also been described. The developed protocol offers recyclability of catalyst for multiple (four) times without any appreciable loss in stability and catalytic reactivity.
Keywords: Click reaction; Cycloaddition; mesoporous materials; SBA-15; Suzuki coupling

Transition-metal-catalyzed reactions involving arynes - Dhokale, Ranjeet A.; Mhaske, Santosh B. (Synthesis-Stuttgart, 2018)
The plethora of transformations attainable by the transition-metal-catalyzed reactions of arynes has found immense contemporary interest in the scientific community. This review highlights the scope and importance of transition-metal-catalyzed aryne reactions in the field of synthetic organic chemistry reported to date. It covers transformations achieved by the combination of arynes and various transition metals, which provide a facile access to a biaryl motif, fused polycyclic aromatic compounds, different novel carbocycles, various heterocycles, and complex natural products. 1 Introduction 2 Insertion of Arynes 3 Annulation of Arynes 4 Cycloaddition of Arynes 5 Multicomponent Reactions of Arynes 6 Miscellaneous Reactions of Arynes 7 Total Synthesis of Natural Products Using Arynes 8 Conclusion
Keywords: annulation; arynes; Cycloaddition; Insertion; multicomponent; Natural products; Transition Metal

Photoinduced multicomponent regioselective synthesis of 1,4,5-trisubstituted-1,2,3-triazoles: transition metal-, azide- and oxidant-free protocol - Sai Allaka, Bhargava; Basavoju, Srinivas; Rama Krishna, Gamidi (Advanced Synthesis & Catalysis, 2021)
A transition metal- and azide-free approach is explored to synthesize 1,4,5-trisubstituted-1,2,3-triazoles under sunlight. The reaction proceeds via C-N and N-N bond formations. These regioselective 1,2,3-triazoles are obtained from isatin Schiff bases, benzaldehydes and tosylhydrazine in the presence of base. This protocol offers the structurally diverse 1,2,3-triazole derivatives with 75-90% yields.
Keywords: 1; 2; 3-triazoles; 4; 5-trisubstituted-1; azide- and oxidant free protocol; Cycloaddition; milder reaction conditions; molecular diversity; Multicomponent reaction; Regioselectivity; transition metal-

Regioselective synthesis of 1,4,5-trisubstituted 1,2,3-triazole derivatives from alpha,beta-unsaturated carbonyls - Verma, Naimish K.; Bera, Smritilekha; Gonnade, Rajesh; Mondal, Dhananjoy (European Journal of Organic Chemistry, 2022)
The copper-catalyzed oxidative azide-olefin cycloaddition (OAOC) reaction of differently substituted alpha,beta-unsaturated carbonyls with azides provided an efficient method for preparing biologically active 1,4,5-trisubstituted 1,2,3-triazoles. In this study, the cycloaddition reaction was found to be a simple and powerful method for constructing diverse mono- and bis-(1,4,5-trisubstituted 1,2,3-triazole) functionalized heterocyclic compounds in moderate to high yields with great regioselectivity. The XRD-analysis data of one of the bis-triazole derivatives supported the regioselectivity as well as the conformity of the method in the construction of the triazole nucleus. The preliminary antifungal profile against C. albicans was observed with cinnamaldehyde-based triazole derivatives demonstrating promising results.
Keywords: alpha; antifungal; beta-Unsaturated carbonyls; Cycloaddition; Dibenzalacetone; Triazole

Transition metal- and oxidant-free regioselective synthesis of 3,4,5-trisubstituted pyrazoles by means of [3+2] cycloaddition reactions - Allaka, Bhargava Sai; Basavoju, Srinivas; Gamidi, Rama Krishna (ChemistrySelect, 2022)
A highly efficient regioselective synthesis of 3,4,5-trisubstituted pyrazoles via transition metal- and oxidant-free, three component [3+2] cycloaddition with thiazolidinedione chalcones, benzaldehydes and N-tosylhydrazine is described. The reaction proceeds through C-C and C-N bond formations under mild reaction conditions to produce structurally diverse polysubstituted pyrazoles in moderate to good yields.
Keywords: 3; 4; 5-trisubstituted pyrazoles; Cycloaddition; Multicomponent reaction; Oxidant free; Regioselectivity; Transition metal free

Metal-free isoamyl nitrite mediated efficient synthesis of 1,2,4-oxadiazoles - Galave, Sharad A.; Kadam, Kishorkumar S.; Sonawane, Amol D.; Pansare, Vaibhav R.; Garud, Dinesh R. (Tetrahedron Letters, 2023)
We report herein, a metal-free isoamyl nitrite mediated efficient synthesis of 1,2,4-oxadiazoles by one pot cycloaddition reaction of aldoximes with nitriles. The structure of the 1,2,4-oxadiazole derivatives was confirmed by studies of spectral analysis. Current methodology provides a novel pathway to access 1,2,4-oxadiazole derivatives.& COPY; 2023 Elsevier Ltd. All rights reserved.
Keywords: 1; 2; 4-Oxadiazole; Aldoxime; Cycloaddition; Isoamyl nitrite

Ionic liquid assisted green synthesis of quinoxaline based bisspirooxindoles: anticancer evaluation and molecular dynamics - Kanchrana, Madhu; Krishna, Gamidi Rama; Dey, Biswajit; Pandey, Nandita; Guru, Santosh Kumar; Sangolkar, Akanksha Ashok; Pawar, Ravinder; Basavoju, Srinivas (CHEMISTRYSELECT, 2024)
Keywords: Cycloaddition; spirooxindoles